ANALYSIS OF FORGING MACHINE EFFECTIVENESS USING OVERALL EQUIPMENT EFFECTIVENESS (OEE) AND SIX BIG LOSSES METHODS (CASE STUDY : PT X) - Al Rizki Dermawan; Yani Iriani (Jurnal Darma Agung, 2022)
PT X is a company in the manufacturing industry, with automotive spare parts being its main product. The current issue at PT X is a production shortage. One of the causes of decreased productivity, according to observations, is that there is still waste in the form of waiting time produced by a variety of factors such as workers, machines, and materials. The forging machine factor is the problem that contributes the most to PT X. The problem is that waiting is often inefficient because the product is of poor quality. The purpose of this research was to determine the value of Overall Equipment Effectiveness (OEE) on fitting forging machines and to identify issues in the production line using Six Big Losses. The Overall Equipment Effectiveness (OEE) method is a comprehensive performance measurement related to the availability of quality and productivity processes, whereas the Six Big Losses are equipment failure, set up and adjustment losses, idling and minor stoppages, reduced speed losses, quality defects and rework, and reduced yield or scrap losses. According to the findings of this survey, the average OEE value is 83.84%. As a result, it falls under the category of not meeting the standards. While calculating the Six Big Losses, the most common type of waste is the lower yield or scrap loss of 4.25%. Improvement efforts are focused mostly on the quality line, with the 4M+1E (Man, Machine, Material, Method, and Environment) factor influencing the low OEE value. The machine factor is the most important contributor to the appearance of shape change or product reject deformation in the 4M+1E analysis. Thus, PT X must enhance the temperature parameter settings and the length of the pressing process to reduce shape rejects.